Use of non-specific immunoglobulins in Catalonia in three third-level hospitals: a descriptive analysis of a hospital-prescribed medication registry - Riera-Arnau, J.; Ballarín, E.; Llop, R.; Montané, E.; Hereu, P.; Vancells, G.; Padullés-Zamora, N.; Barriocanal, A. M.; Cardona-Peitx, G.; Casasnovas, C.; Montoro, J. B.; Nuñez, M.; et al. (Frontiers in Pharmacology, 2024)
Background: The increasing use of non-specific immunoglobulins (NSIG) and current shortage show a need of NSIGs' use prioritization. Data from clinical perspective are necessary, mainly for pediatric patients. Objectives: To assess the level of clinical evidence (LoE) of the indications NSIGs are used for, the reasons for discontinuation and the costs invested. Methods: A retrospective multicentric study was conducted on NSIGs incident users between September-2019 and December-2021 retrieved from the Registry of Patients and Treatments (RPT) from Catalonia (Spain). LoE were categorized as A) authorized indications; B) unauthorized with scientific support; C) unauthorized without support; and UNK) unknown, following local and United Kingdom's guidelines as a sensitivity analysis. We also estimated overall spendings and costs per patient-visit.Results: 400 patients were included (17.3% pediatric) with a mean follow-up of 122.1/personyears for adults. Most frequent indications were nervous system and blood diseases. Almost all pediatric patients (56;81.2%) were treated under A-level indications as for the 217 (65.6%) of adults. In the sensitivity analysis, A-level usage rate decreased to one-third and B-level increased by 2-3 times. The 37.8% (151) of individuals discontinued. This was predominantly owing to remission or no-response. Total costs were 868,462.6€/year and median spendings per visit, 1,500€ for adults and 700€ pediatrics.Conclusions: NSIGs are used in clinical practice mainly for approved indications, despite nonapproved indications are still an important matter. This could represent a significant economic burden on the healthcare system, keeping focus on the pediatric population and those at risk for discontinuation with alternative therapeutical options.